Respiratory failure and bioelectrical phase angle are independent predictors for long-term survival in acute heart failure. (31st December 2022) - Scicchitano, Pietro; Ciccone, Marco Matteo; Iacoviello, Massimo; Guida, Piero; De Palo, Micaela; Potenza, Angela; Basile, Marco; Sasanelli, Paolo; Trotta, Francesco; Sanasi, Mariella; Caldarola, Pasquale; Massari, Francesco
Abstract: Background. The assessment of long-term mortality in acute decompensated heart failure (ADHF) is challenging. Respiratory failure and congestion play a fundamental role in risk stratification of ADHF patients. The aim of this study was to investigate the impact of arterial blood gases (ABG) and congestion on long-term mortality in patients with ADHF. Methods and results. We enrolled 252 patients with ADHF. Brain natriuretic peptide (BNP), blood urea nitrogen (BUN), phase angle as assessed by means of bioimpedance vector analysis, and ABG analysis were collected at admission. The endpoint was all-cause mortality. At a median follow-up of 447 d (interquartile range [IQR]: 248–667), 72 patients died 1–840 d (median 106, IQR: 29–233) after discharge. Respiratory failure types I and II were observed in 78 (19%) and 53 (20%) patients, respectively. The ROC analyses revealed that the cut-off points for predicting death were: BNP > 441 pg/mL, BUN > 1.67 mmol/L, partial pressure in oxygen (PaO2 ) ≤69.7 mmHg, and phase angle ≤4.9°. Taken together, these four variables proved to be good predictors for long-term mortality in ADHF (area under the curve [AUC] 0.78, 95% CI 0.72–0.78), thus explaining 60% of all deaths. A multiparametric score based on these variables was determined: each single-unit increase promoted a 2.2-fold augmentation of the risk for death (hazard ratio [HR] 2.2, 95% CI 1.8–2.8, p < .0001). Conclusions. A multiparametric approach based on measurements of BNP, BUN, PaO2, and phase angle is a reliable approach for long-term prediction of mortality risk in patients with ADHF.